Adobe After Effects 7.0 studio techniques - Christiansen, Mark (Visual effects specialist) (Adobe Press, 2006)
"Ready to learn the stunning visual effects techniques used at such leading-edge studios as Industrial Light & Magic and The Orphanage? Adobe After Effects 7.0 Studio Techniques instructs and inspires you with real-world examples and insider techniques. With this in-depth guide to Adobe's updated motion graphics and effects powerhouse, you'll get complete coverage of all the big features in After Effects 7.0: high dynamic range (HDR) 32-bit per channel color compositing, a redesigned user interface, a new Graph Editor, and dozens of other enhancements. This book goes beyond conventional step-by-step instruction, teaching you bread-and-butter effects that you can adapt and combine for countless projects. Book jacket."--Jacket.